HUBUNGAN DAYA LEDAK LENGAN DAN DAYA LEDAK TUNGKAI TERHADAP KEMAMPUAN SMASH BOLAVOLI - Kamadi, La (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2020)
The problem in this study is the relationship between the explosive power of the arms, the explosive power of the legs and hand eye coordination on the smash ability in the volleyball game of the students of FIK UNM. The population in this study were all students of FIK UNM sports coaching education with a total sample of 30 students who were selected by random sampling. The data analysis technique used is the correlation and regression analysis technique using the SPSS version 16 system at a significant level of 95% or Î± 0.05. Starting from the results of data analysis, this study concludes that: (1) The correlation between arm explosive power and smash ability in volleyball, proved to be r0 = 0.955 (P <Î± 0.05), (2) The relationship between limb explosive power and smash ability at volleyball game, proved to be r0 = 0.917 (P <Î±0.05), (3) The relationship between hand eye coordination and smash ability in volleyball games, proved to be R0 = 0.852 (P <Î± 0.05), (4) Relationship of arm explosive power , limb explosive power and hand eye coordination on smash ability in volleyball game proved to be r0 = 0.970 (P <Î±0.05). This can be explained that if a student is supported by good explosive power, leg explosive power and ankle coordination, the student can do a good smash too.